Improvement of Inventory Control Using Continuous Review Policy in A Local Hospital at Bandung City, Indonesia - Hafnika, Fina; Farmaciawaty, Desy Anisya; Adhiutama, Akbar; Basri, Mursyid Hasan (The Asian Journal of Technology Management (AJTM), 2016)
Abstract. This research was aimed to analyze the excess inventories issue in pharmacy and medical equipment unit at a local hospital in Bandung which affected the service level of the hospital. As one of the busy hospital in Java, proven by the higher amount of the patient/year than in other average Java typical hospital, the hospital needs to concern about the pharmaceutical and medical equipment inventories in order to fulfill patientsâ€™ needs and in the same time keeping the inventory level under control. Therefore, an inventory control evaluation was conducted to determine the appropriate number of inventories and time of order to avoid the excessive goods in central warehouse of the hospital. By using probabilistic inventory model and continuous review policy, the pharmaceutical inventory in the hospital was calculated to compare the ideal and actual amount of the average inventory level (AIL). ABC (Always, Better, Control) classification also classified in this research to identify the proper item which potentially can be reduced from the inventory. From the analysis, we have discovered that the hospital potentially able to reduce almost Rp 830 million or 57% from the overstock inventory level by using continuous review policy as the basis of inventory control calculation system.Keywords: Â Continuous review policy, inventory control, EOQ, ROP, AIL